Addressing the role of surgery in brain tumour trials: A report from the neurosurgery committee of the EORTC brain tumour group - Duerinck, Johnny; Karschnia, Philipp; Broekman, Marike; Gempt, Jens; Petrescu, George E.D.; Jakola, Asgeir S.; Grossman, Rachel; Goldbrunner, Roland; Jenkinson, Michael D.; Widhalm, Georg; Neidert, Marian; Picart, Thiebaud; et al. (European Journal of Cancer, 2025)
The Brain Tumor Group (BTG) of the European Organization for Research and Treatment of Cancer (EORTC) conducts academic clinical trials and translational research to improve clinical management of patients with primary and secondary brain tumors. The EORTC BTG has traditionally played an important role in providing evidence and thus advancing the field, albeit with a main focus on radiotherapy and pharmacotherapy in gliomas. Although examples of well-designed neuro-oncological surgical trials can be found, evidence in surgical neuro-oncology predominantly includes data from uncontrolled prospective series or retrospective cohorts. By means of a thorough literature and EORTC database review, we demonstrate, firstly, that while the pathway of the neuro-oncology patient most often starts with neurosurgery, its several aspects have traditionally been poorly acknowledged in clinical trials in neuro-oncology. We also show that the definitions and methods of assessment vary greatly between studies, limiting generalizability. The newly established Neurosurgery Committee of the EORTC BTG aims to address this gap by increasing the number of prospective surgical trials, but also the involvement of neurosurgeons in clinical trial design, promoting standardized terminology for description of the surgical aspects, including extent of resection. We will also explore alternative trial designs when randomization is deemed difficult, as well as focus on defining surgical quality indicators that influence outcome. By addressing these challenges, the committee aims to enhance the quality of neurosurgical evidence in neuro-oncology and define optimal surgical methods and standards of care. This should ultimately improve outcomes and quality of life for patients with brain tumors through evidence-based surgical interventions.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Brain Tumor trials; Neurosurgery; Surgical trials